FAILURE MODE AND EFFECT ANALYSIS (FMEA) AS TREATMENT OF PREDICTIVE PREVENTION AND LEAKAGE OF BOILER TYPE BALANCE DRAF FAN - Muhammad Nurtanto; Ita Novita Sari; Sulaeman Deni Ramdani; Moh Fawaid (VANOS Journal of Mechanical Engineering Education, 2018)
Risk analysis aims to prevent the incompatibility of a system used in the testing process including the Boiler system. At the Labuan 2 Steam Power Plant (PLTU) 2, the Boiler component was declared "very often" to have a pipe leak. Failure Mode And Effect Analysis (FMEA) is a method used to analyze the risk of failure. This method is represented by calculating the value of RPN (Risk Priority Number) obtained from the results of the multiplication of S (severty), O (occurrence), and D (detection). The highest analysis results are shown at 480 (in the steam drum component in the form of abnormal steam and water level failure). The cause is human error. Next three levels below are (1) Economizer component, which is 360 causes of combustion side ash erosion, material lifetime, and economizer tube fibration; (2) super heater tube and re-heater tube components which are 320 due to Corrosion, Overheat Flyash erosion, Sub blower erosion, Welding error; and (3) Walltube which is 320 causes of overheating and sub blower erosion. The recommendation for the analysis of FMEA testing to predict mantenance is done by applying remaining life assessment after 8,000 hours / operational.